The street-level delivery of activation policies: constraints and possibilities for a practice of citizenship. Issue 3 (3rd July 2016) - Nothdurfter, Urban
Abstract : The debate on activation policies and challenges to social citizenship has to go beyond the level of formal policy and take into account also its operational and street-level dimension, which shapes what eventually arrives as policy on the ground. In this context, frontline practice plays a crucial role since it constitutes the very moment when activation policies encounter their target groups and real-world solutions have to be found. This article outlines a conceptual framework to approach frontline work within the context of activation and presents the main findings of a research project aimed at exploring the challenges, interpretations and reactions of frontline practitioners in Public Employment Services in the cities of Vienna (Austria) and Milan (Italy). The findings contribute to the debate on the constraints and possibilities for a practice of citizenship in a practice field whose challenges are often neglected both by social policy and social work research although it has become a central arena for welfare state intervention in which social citizenship, eventually, becomes manifest. Particular attention is paid to different framings of practice and to the questions whether and to what extent professionalising 'activation work' could counteract the precarious and highly individualised role of frontline practitioners in this ambiguous public domain.